Ślub i zdrada jako elementy obyczajowości mieszczan angielskich w drugiej połowie XVII wieku - Kicińska, Dorota (Acta Universitatis Lodziensis. Folia Historica, 2010)
Marriage and adultery were very important parts of middle- class life in 17th c. England (writing middle class I mean townspeople, as the biggest part of this class). The great opportunity to discover 17th c. townspeople culture and customs give us The Diary by Samuel Pepys. Very helpful can also be Small Books and Pleasant Histories. Popular Fiction ond its Readership an Seventeenth-Century England by Margareth Spufford. In this book writer analyzed Merry and Godly Books – a two-penny booklet very popular in 17th c., which in excellent way describes the reality of that age. The 17th c. Londoners could marry in several different ways. From the simple private promise, through Clandestine and later Fleet marriages, to License marriages and official Church Carriages. Every of this ways had their advantages and disadvantages, for example Fleet Carriages were cheap, but secret and hasty form of ceremony, usually without members of family, could bring danger of bigamy and other iniquities or abuses. In the process of finding beloved person the will of parents were important but not the most. It seems that men and women from middle class chose whom they would marriage by themselves. The friends and parents could help them, but they couldn’t force them. While looking for a good partner young people tried not to forget about material aspects, however money wasn't the most important issue. It seems that perfect husband or wife should be at first honesty, dutiful or affectionate, modest and should know how to behave in company. The adulteries were very common but, as I think, not compared with marriage virtue. Samuel Pepys had many mistress but his relations with wife were rather happy and harmonious despite the fact that they had no children. Even after death of Elizabeth he didn’t marry again. On the other hand adultery had to be kept in secret in order not to lose good name by person who was unfaithful.